Nerve growth factor withdrawal-induced cell death in neuronal PC12 cells resembles that in sympathetic neurons (The Rockefeller University Press, 1992)
Previous studies have shown that in neuronal cells the developmental phenomenon of programmed cell death is an active process, requiring synthesis of both RNA and protein. This presumably reflects a requirement for novel gene products to effect cell death. It is shown here that the death of nerve growth factor-deprived neuronal PC12 cells occurs at the same rate as that of rat sympathetic neurons and, like rat sympathetic neurons, involves new transcription and translation. In nerve growth factor-deprived neuronal PC12 cells, a decline in metabolic activity, assessed by uptake of [3H]2-deoxyglucose, precedes the decline in cell number, assessed by counts of trypan blue-excluding cells. Both declines are prevented by actinomycin D and anisomycin. In contrast, the death of nonneuronal (chromaffin-like) PC12 cells is not inhibited by transcription or translation inhibitors and thus does not require new protein synthesis. DNA fragmentation by internucleosomal cleavage does not appear to be a consistent or significant aspect of cell death in sympathetic neurons, neuronal PC12 cells, or nonneuronal PC12 cells, notwithstanding that the putative nuclease inhibitor aurintricarboxylic acid protects sympathetic neurons, as well as neuronal and nonneuronal PC12 cells, from death induced by trophic factor removal. Both phenotypic classes of PC12 cells respond to aurintricarboxylic acid with similar dose-response characteristics. Our results indicate that programmed cell death in neuronal PC12 cells, but not in nonneuronal PC12 cells, resembles programmed cell death in sympathetic neurons in significant mechanistic aspects: time course, role of new protein synthesis, and lack of a significant degree of DNA fragmentation.